Resin composition and thermally conductive sheet

A resin composition with an epoxy resin, a polybutadiene structured coupling agent, and an inorganic filler addresses the insufficient thermal conductivity and adhesiveness issues of existing compositions, achieving enhanced thermal conductivity and adhesiveness to metal-based circuit boards.

JP7604241B2Active Publication Date: 2024-12-23NITTO SHINKO KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021005800
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-18
Publication Date
2024-12-23
Estimated Expiration
2041-01-18

AI Technical Summary

Technical Problem

Existing resin compositions containing epoxy resin, curing agent, and inorganic filler, such as those described in Patent Document 1, do not achieve sufficient thermal conductivity and adhesiveness to adherends when cured, particularly when used on metal-based circuit boards.

Method used

A resin composition comprising an epoxy resin, a coupling agent with a polybutadiene structure, a curing agent, and an inorganic filler, where the inorganic filler is dispersed in the epoxy resin, utilizing a silane coupling agent to enhance thermal conductivity and adhesiveness by connecting the polymerizable component and inorganic filler.

Benefits of technology

The resin composition achieves sufficient thermal conductivity and high adhesiveness to adherends like metal-based circuit boards, with improved cohesive failure strength and thermal conductivity when cured, using a silane coupling agent with a polybutadiene structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604241000007
    Figure 0007604241000007
  • Figure 0007604241000008
    Figure 0007604241000008
  • Figure 0007604241000001
    Figure 0007604241000001
Patent Text Reader

Abstract

To provide a resin composition or the like that can be cured into a product to show sufficient thermal conductivity and high adhesion to an adherend.SOLUTION: The resin composition contains an epoxy resin, a silane coupling agent, a curing agent, and an inorganic filler, the inorganic filler being dispersed in the epoxy resin, the silane coupling agent having a polybutadiene structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a thermally conductive sheet. [Background technology]

[0002] 2. Description of the Related Art Conventionally, in the field of electronics, a resin composition containing an epoxy resin, a curing agent, and an inorganic filler has been used.

[0003] Patent Document 1 listed below discloses that a resin composition containing an epoxy resin, a curing agent, and an inorganic filler is cured and used as a heat dissipation sheet. Such a heat dissipating sheet has heat dissipation properties because it contains a relatively large amount of inorganic filler such as boron nitride filler. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-94887 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, although the resin composition described in Patent Document 1 contains a relatively large amount of inorganic filler as described above, there is a problem in that the thermal conductivity (heat dissipation property) of the cured product is not necessarily sufficient.

[0006] Furthermore, since the resin composition described in Patent Document 1 is used by adhering it to an adherend such as a metal-base circuit board, it is required that the cured product exhibit high adhesion to the adherend, but it cannot be said that sufficient research has been conducted on this point yet.

[0007] Therefore, an object of the present invention is to provide a resin composition that, when cured, exhibits sufficient thermal conductivity and high adhesion to an adherend, and a thermally conductive sheet having a resin layer composed of the resin composition. [Means for solving the problem]

[0008] As a result of intensive research, the present inventors have found that in a resin composition containing an epoxy resin, a coupling agent, a curing agent, and an inorganic filler, in which the inorganic filler is dispersed in the epoxy resin, by using an inorganic filler treated with a specific silane coupling agent as the inorganic filler, when a cured product is formed, the thermal conductivity of the cured product is sufficiently high and the adhesion of the cured product to an adherend is sufficiently high, which led to the invention.

[0009] That is, the resin composition according to the present invention is a resin composition containing an epoxy resin, a coupling agent, a curing agent, and an inorganic filler, the inorganic filler being dispersed in the epoxy resin, The silane coupling agent has a polybutadiene structure.

[0010] According to this configuration, the resin composition, when cured, exhibits sufficient thermal conductivity and high adhesiveness to an adherend such as a metal base circuit board.

[0011] In addition, in the resin composition according to the present invention, The silane coupling agent is a block copolymer having a plurality of blocks, The block copolymer comprises a polybutadiene block, It is preferable that the polymer further contains a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group at both ends of the molecule.

[0012] According to this configuration, the resin composition, when cured, exhibits more sufficient thermal conductivity and more excellent adhesion to adherends such as metal base circuit boards.

[0013] The block copolymer is a first polybutadiene block composed of an addition polymer of unsubstituted butadiene having no functional group; and a second polybutadiene block composed of an addition polymer of butadiene having an acid anhydride group.

[0014] According to this configuration, the resin composition exhibits more sufficient thermal conductivity when it becomes a cured product.

[0015] In addition, in the resin composition according to the present invention, The inorganic filler preferably includes a boron nitride filler.

[0016] According to this configuration, the resin composition, when cured, exhibits more sufficient thermal conductivity and more excellent adhesion to adherends such as metal base circuit boards.

[0017] A thermally conductive sheet according to the present invention is a thermally conductive sheet including a resin layer made of a resin composition containing an epoxy resin, a coupling agent, a curing agent, and an inorganic filler, the inorganic filler being dispersed in the epoxy resin, The silane coupling agent has a polybutadiene structure.

[0018] According to such a configuration, the thermally conductive sheet exhibits sufficient thermal conductivity when the resin composition becomes a cured product, and also exhibits high adhesion to an adherend such as a metal base circuit board.

[0019] In addition, in the thermally conductive sheet according to this embodiment, The silane coupling agent is a block copolymer having a plurality of blocks, The block copolymer comprises a polybutadiene block, It is preferable that the polymer further contains a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group at both ends of the molecule.

[0020] According to this configuration, when the resin composition becomes a cured product, the thermally conductive sheet exhibits more sufficient thermal conductivity and also exhibits more excellent adhesion to an adherend such as a metal base circuit board.

[0021] In addition, in the thermally conductive sheet according to this embodiment, The block copolymer is a first polybutadiene block composed of an addition polymer of unsubstituted butadiene having no functional group; and a second polybutadiene block composed of an addition polymer of butadiene having an acid anhydride group.

[0022] According to this configuration, the thermally conductive sheet exhibits more sufficient thermal conductivity when the resin composition becomes a cured product.

[0023] In addition, in the thermally conductive sheet according to the present invention, The inorganic filler preferably includes a boron nitride filler.

[0024] According to this configuration, when the resin composition becomes a cured product, the thermally conductive sheet exhibits more sufficient thermal conductivity and also exhibits more excellent adhesion to an adherend such as a metal base circuit board. Effect of the Invention

[0025] According to the present invention, it is possible to provide a resin composition that, when cured, exhibits sufficient thermal conductivity and high adhesion to an adherend, and a thermally conductive sheet having a resin layer composed of the resin composition. [Brief description of the drawings]

[0026] [Figure 1] FIG. 2 is a top view showing the etched stack. [Diagram 2] FIG. 4 is a cross-sectional view showing an arrangement for measuring a withstand voltage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Hereinafter, one embodiment of the present invention will be described.

[0028] (Resin composition) The resin composition according to the present embodiment contains a component that will ultimately constitute a cured product, that is, the resin composition according to the present embodiment contains a polymerizable component that will become a cured resin by polymerization. The resin composition according to the present embodiment also contains an inorganic filler so that the cured product has good thermal conductivity after curing. Furthermore, the resin composition according to the present embodiment contains a silane coupling agent as a coupling agent that functions to connect the polymerizable component and the inorganic filler. The resin composition according to the present embodiment may contain additives that are generally used as plastic compounding chemicals, to the extent that the effects of the present invention are not impaired.

[0029] In the resin composition according to this embodiment, the content of the polymerizable component in 100 parts by mass of the cured product after curing is preferably 10 parts by mass or more and 70 parts by mass or less, and more preferably 30 parts by mass or more and 40 parts by mass or less.

[0030] The cured product obtained by curing the resin composition according to this embodiment preferably contains 10 to 60 parts by volume of inorganic filler, more preferably 30 to 60 parts by volume, and even more preferably 50 to 60 parts by volume, based on 100 parts by volume of solid content. In addition, from the viewpoint that the content ratio of the inorganic filler in the cured product is likely to be within the above-mentioned range, the resin composition according to this embodiment preferably contains 30 parts by mass or more and 90 parts by mass or less of the inorganic filler, and more preferably 60 parts by mass or more and 80 parts by mass or less, per 100 parts by mass of the polymerizable component.

[0031] The resin composition according to the present embodiment contains 0.01 parts by mass or more and 0.03 parts by mass or less of the silane coupling agent with respect to 100 parts by mass of the inorganic filler.

[0032] Furthermore, the resin composition according to this embodiment preferably contains 0.005 parts by mass or more and 0.05 parts by mass or less, and more preferably 0.01 parts by mass or more and 0.03 parts by mass or less, of the additive relative to 100 parts by mass of the inorganic filler.

[0033] The resin composition according to the present embodiment contains an epoxy resin and a curing agent as the polymerizable component. In the present embodiment, the epoxy resin is cured together with the curing agent to become a cured resin.

[0034] The ratio of the total amount of the epoxy resin and the curing agent in the polymerizable component is preferably 80% by mass or more and 100% by mass or less, and more preferably 90% by mass or more and 100% by mass or less.

[0035] The ratio of the equivalent of the curing agent to the equivalent of the epoxy resin is preferably 1 / 2 or more and 2 / 1 or less, and more preferably 2 / 3 or more and 3 / 2 or less.

[0036] The epoxy resin has a plurality of epoxy groups in its molecular structure, and examples of the epoxy resin include bisphenol A type epoxy resin, novolac type epoxy resin, cyclic aliphatic type epoxy resin, long chain aliphatic epoxy resin, glycidyl ester type epoxy resin, and glycidyl amine type epoxy resin.

[0037] Examples of the curing agent include amine-based curing agents, phenol-based curing agents, and acid anhydrides. Examples of the amine-based curing agent include diaminodiphenylsulfone, diaminoaminediamide, diaminodiphenylmethane, and triethylenetetramine. Examples of the phenol-based hardener include phenol novolac resin, aralkyl-type phenol resin, dicyclopentadiene-modified phenol resin, naphthalene-type phenol resin, and bisphenol-based phenol resin. Examples of the acid anhydride include phthalic anhydride, trimellitic anhydride, and maleic anhydride.

[0038] Examples of the inorganic filler include boron nitride filler (BN filler), aluminum nitride filler, silicon nitride filler, gallium nitride filler, alumina filler, silicon carbide filler, silicon dioxide filler, magnesium oxide filler, and diamond filler.

[0039] The resin composition according to the present embodiment preferably contains, as the inorganic filler, a boron nitride filler having excellent thermal conductivity. Although boron nitride fillers have excellent thermal conductivity, they have a relatively small number of surface functional groups (OH, etc.) involved in polymerization. Therefore, in a resin composition that contains a boron nitride filler and does not contain the silane coupling agent, it is difficult to increase the affinity between the polymerizable component and the boron nitride filler because the boron nitride filler has a small number of surface functional groups. However, the resin composition according to the present embodiment contains the silane coupling agent. As described later, the silane coupling agent has a functional group having affinity to the surface functional group of the inorganic filler and a functional group having affinity to the polymerizable component. Therefore, even if the resin composition contains a boron nitride filler with a relatively small number of surface functional groups, the silane coupling agent can play a role of connecting the polymerizable component and the boron nitride filler. As a result, when the resin composition according to the present embodiment is cured, the cohesive fracture strength of the cured product is increased. As a result, when a boron nitride filler having excellent thermal conductivity is contained as the inorganic filler, when the resin composition according to this embodiment becomes a cured product, the thermal conductivity of the cured product can be increased while the cohesive fracture strength can be increased. Furthermore, by changing the content of the boron nitride filler, it is possible to adjust the thermal conductivity and cohesive fracture strength of the cured product.

[0040] The inorganic filler preferably contains aggregate particles formed by agglomerating a plurality of primary particles.

[0041] In the resin composition according to this embodiment, the silane coupling agent has a polybutadiene structure. That is, the silane coupling agent is a polymer having a constituent unit derived from butadiene and a constituent unit derived from a silane coupling agent having a polymerizable functional group. The silane coupling agent preferably has, as the polymerizable functional group, a functional group capable of addition polymerization rather than a functional group capable of condensation polymerization. The addition-polymerizable functional group may, for example, be a vinyl group. The vinyl group does not have to be provided in the form of an ethenyl group, and may be provided in the molecular chain of the silane coupling agent in the form of an isopropenyl group. Furthermore, the ethenyl group may be provided in the molecular chain of the silane coupling agent as a part of a vinylphenyl group or an acrylic group. The isopropenyl group may be present in the molecular chain of the silane coupling agent as part of a methacryl group. Therefore, the silane coupling agent is preferably a compound having the structure shown in (1a) below. The following compound may be either a block copolymer or a random copolymer. In the compound having the structure shown in (1a), the molecular terminals (Rx, Ry) may be any of a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 3 carbon atoms, and a carbonyl group. The molecular ends (Rx, Ry) may have the same structure or different structures on one end (Rx) and the other end (Ry).

[0042] [ka] (In formula (1a), R is a methyl group or an ethyl group, a is an integer of 1 or more and 25 or less, b is an integer of 1 or more and 25 or less, and Z indicates that the alkoxysilyl group is bonded to the main chain directly or via a heteroatom, or is bonded to the main chain via an organic group.)

[0043] In order to more suitably exhibit rubber elasticity, the a is preferably an integer of 2 or more.

[0044] In the compound having the structure shown in (1a), the total number of repeating structural units (a+b) may be, for example, 15 or more and 40 or less. Furthermore, when Z in the formula is an organic group, the organic group can have 1 or more and 20 or less carbon atoms, for example.

[0045] The silane coupling agent is preferably a block copolymer having a plurality of blocks, and the block copolymer preferably contains a polybutadiene block and further contains a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group (Si(OR)3) at both ends of the molecule. Moreover, it is more preferable that the silane coupling agent is a block copolymer of a polybutadiene block and a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group, as shown in the following formula (1b). Commercially available silane coupling agents such as those represented by the following formula (1b) include, for example, those under the trade name "X-12-1267B" (manufactured by Shin-Etsu Silicones) and those under the trade name "X-12-1267B-ES" (manufactured by Shin-Etsu Silicones).

[0046] [ka] (In formula (1b), R is a methyl group or an ethyl group, a is an integer of 2 or more and 25 or less, b is an integer of 2 or more and 25 or less, and Z indicates that the alkoxysilyl group is bonded to the main chain directly or via a heteroatom, or is bonded to the main chain via an organic group.)

[0047] As described above, when the a is an integer of 2 or more, rubber elasticity can be suitably exhibited.

[0048] In the silane coupling agent, the block copolymer may include a first polybutadiene block composed of an addition polymer of unsubstituted butadiene having no functional group, and a second polybutadiene block composed of an addition polymer of butadiene having an acid anhydride group. Furthermore, the silane coupling agent may be a block copolymer of the first polybutadiene block, the second polybutadiene block, and a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group, as shown in the following formula (2a). An example of a commercially available silane coupling agent as represented by the following formula (2a) is a product under the trade name "X-12-1287A" (manufactured by Shin-Etsu Silicones Co., Ltd.).

[0049] [ka] (In formula (2a), R is a methyl group or an ethyl group, a is an integer of 1 to 20, b is an integer of 2 to 8, c is an integer of 1 to 25, and Z indicates that the alkoxysilyl group is bonded to the main chain directly or via a heteroatom, or is bonded to the main chain via an organic group.)

[0050] In order to more suitably exhibit rubber elasticity, the a is preferably an integer of 2 or more.

[0051] Incidentally, the reason why the resin composition according to this embodiment exhibits sufficient thermal conductivity when cured and also exhibits high adhesion to adherends such as metal base plates has not been fully elucidated, but the inventor believes the reason for this to be as follows.

[0052] As shown in the above formula (1a), the silane coupling agent having a polybutadiene structure has a double bond derived from the polybutadiene structure in its structure. Also, the epoxy resin has an aromatic ring. That is, the epoxy resin also has a double bond derived from the aromatic ring. Therefore, as described above, when the resin composition according to the present embodiment contains epoxy resin as the polymerizable component, and contains the silane coupling agent having polybutadiene structure as the silane coupling agent, the affinity between the polymerizable component and the silane coupling agent having polybutadiene structure in the resin composition is increased, and the compatibility of the silane coupling agent having polybutadiene structure with the polymerizable component is increased.Therefore, it is considered that the silane coupling agent having polybutadiene structure is sufficiently dispersed in the polymerizable component in the resin composition. Furthermore, it is believed that a silane coupling agent having a polybutadiene structure exhibits properties similar to those of rubber, that is, rubber elasticity, due to the polybutadiene structure. That is, in the resin composition according to the present embodiment, it is considered that the silane coupling agent having a polybutadiene structure, which is considered to exhibit rubber elasticity, is sufficiently dispersed in the polymerizable component, and therefore, when the resin composition is cured, the occurrence of cohesive failure in the cured product can be suppressed, and this is considered to result in excellent adhesion to adherends such as metal-based circuit boards.

[0053] Furthermore, the resin composition according to this embodiment contains a silane coupling agent as shown in the above formula (1a). In the silane coupling agent, the OR group bonded to the Si atom shows affinity to the surface functional group of the inorganic filler, and the polybutadiene block (including the first polybutadiene block and the second polybutadiene block) shows affinity to the polymerizable component. Therefore, in the resin composition according to this embodiment, the inorganic filler and the silane coupling agent are connected via the OR group, and the polymerizable component is connected via the polybutadiene block. That is, the inorganic filler and the polymerizable component are connected via the silane coupling agent. In this way, it is considered that the inorganic filler and the polymerizable component are connected via the silane coupling agent, and when the resin composition is cured to become a cured body, it shows sufficient thermal conductivity.

[0054] As a result of the above, the present inventors believe that the resin composition according to this embodiment, when cured, exhibits sufficient thermal conductivity and also exhibits high adhesion to adherends such as metal lead substrates.

[0055] Examples of the additives include a curing accelerator that accelerates the curing reaction between the epoxy resin and the curing agent, as well as a dispersant, a tackifier, an antiaging agent, an antioxidant, a processing aid, a stabilizer, an antifoaming agent, a flame retardant, a thickener, and a pigment.

[0056] Examples of the hardening accelerator include tetraphenylphosphonium tetraphenylborate, imidazoles, triphenylphosphate (TPP), amine-based hardening accelerators, etc. Examples of the amine-based hardening accelerator include boron trifluoride monoethylamine, etc.

[0057] The resin composition according to the present embodiment preferably contains 0.5 parts by mass or more and 1.5 parts by mass or less of the curing accelerator, and more preferably 0.5 parts by mass or more and 1.0 part by mass or less, per 100 parts by mass of the epoxy resin and the curing agent in total.

[0058] The resin composition according to the present embodiment may be in a state where the curing reaction has progressed to some extent but has not yet been completely cured. In other words, the resin composition may be in a state where the curing reaction has progressed in a part of the resin composition. For example, the resin composition may be coated in a sheet form in a fluid state and then partially cured. Even in a state where the curing reaction has progressed in a part, the resin composition according to the present embodiment contains the above-mentioned epoxy resin, the above-mentioned curing agent, and the above-mentioned inorganic filler.

[0059] (Method of producing resin composition) The method for producing a resin composition according to this embodiment includes a primary kneading step of primarily kneading an epoxy resin, a curing agent, and a silane coupling agent having a polybutadiene structure to obtain a primary kneaded liquid, and a secondary kneading step of adding an inorganic filler to the primary kneaded liquid and secondary kneading the inorganic filler and the primary kneaded liquid to obtain a secondary kneaded liquid. In the method for producing the resin composition according to this embodiment, a pretreatment step for connecting the inorganic filler and the silane coupling agent before kneading with a polymerizable component such as an epoxy resin is not required, i.e., no equipment for the pretreatment step is required, and the primary kneading step and the secondary kneading step can be carried out in a single facility. Therefore, the resin composition can be obtained by a relatively simple method. In addition, since the silane coupling agent having a polybutadiene structure is a liquid material having a moderate viscosity, in the primary kneading process, it is sufficiently kneaded with a polymerizable component such as an epoxy resin, so that the silane coupling agent having a polybutadiene structure and the polymerizable component such as an epoxy resin are sufficiently bonded to each other, and in the secondary kneading process, the silane coupling agent having a polybutadiene structure sufficiently bonded to the polymerizable component such as an epoxy resin can also be sufficiently bonded to the inorganic filler.

[0060] Moreover, in the method for producing a resin composition according to this embodiment, in the primary kneading step, the silane coupling agent is sufficiently dispersed in a polymerizable component such as an epoxy resin, and then an inorganic filler is added and the secondary kneading step is carried out. Therefore, in the resin composition, the polymerizable component such as an epoxy resin and the inorganic filler can be evenly linked via the silane coupling agent.

[0061] In the method for producing a resin composition according to the present embodiment, the silane coupling agent having a polybutadiene structure is preferably a block copolymer having a plurality of blocks, and the block copolymer preferably includes a polybutadiene block and further includes a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group (Si(OR)3) at both ends of the molecule. Moreover, it is more preferable that the silane coupling agent is a block copolymer of a polybutadiene block and a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group, as shown in the following formula (1b).

[0062] [ka] (In formula (1b), R is a methyl group or an ethyl group, a is an integer of 1 or more and 25 or less, b is an integer of 1 or more and 25 or less, and Z indicates that the alkoxysilyl group is bonded to the main chain directly or via a heteroatom, or is bonded to the main chain via an organic group.)

[0063] In addition, in the silane coupling agent having a polybutadiene structure, the block copolymer may include a first polybutadiene block composed of an addition polymer of unsubstituted butadiene having no functional group, and a second polybutadiene block composed of an addition polymer of butadiene having an acid anhydride group. Furthermore, the silane coupling agent may be a block copolymer of the first polybutadiene block, the second polybutadiene block, and a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group, as shown in the following formula (2a).

[0064] [ka] (In formula (2a), R is a methyl group or an ethyl group, a is an integer of 1 to 20, b is an integer of 2 to 8, c is an integer of 1 to 25, and Z indicates that the alkoxysilyl group is bonded to the main chain directly or via a heteroatom, or is bonded to the main chain via an organic group.)

[0065] In the method for producing a resin composition according to this embodiment, the inorganic filler preferably contains a boron nitride filler. The inorganic filler preferably contains aggregated particles formed by agglomerating a plurality of primary particles.

[0066] (Thermal Conductive Sheet) The thermally conductive sheet according to the present embodiment includes a resin layer made of the above-mentioned resin composition, and therefore has improved thermal conductivity.

[0067] The material of the adherend of the thermally conductive sheet is preferably a metal, more specifically, a metal containing copper or aluminum.

[0068] The thermally conductive sheet according to the present embodiment can be used in a metal base circuit board. The metal base circuit board is configured, for example, by bonding a circuit layer to a thermally conductive sheet. Since the metal base circuit board configured in this manner has the thermally conductive sheet according to the present embodiment, the thermal conductivity of the metal base circuit board is also improved.

[0069] Furthermore, the thermally conductive sheet according to the present embodiment is used, for example, in a power module. The power module is configured, for example, by mounting heat generating elements such as semiconductor chips and power ICs on the circuit layer of the metal base circuit board, sealing these elements once with silicone gel, and then performing resin molding on the silicone gel. Since the power module configured in this way has the thermally conductive sheet according to the present embodiment, the thermal conductivity of this power module is also improved.

[0070] The resin composition and the thermally conductive sheet according to the present invention are not limited to the above-mentioned embodiment. The resin composition and the thermally conductive sheet according to the present invention are not limited by the above-mentioned action and effect. The resin composition and the thermally conductive sheet according to the present invention can be modified in various ways without departing from the gist of the present invention. EXAMPLES

[0071] Next, the present invention will be described in more detail with reference to examples and comparative examples. Note that the following examples are intended to explain the present invention in more detail, and are not intended to limit the scope of the present invention.

[0072] Example 1 Epoxy resin A, phenolic resin A, silane coupling agent A, and a curing accelerator were kneaded together to obtain a primary kneaded liquid, and then an inorganic filler was added to the primary kneaded liquid. The primary kneaded liquid and the inorganic filler were kneaded together to obtain a secondary kneaded liquid, thereby obtaining the resin composition of Example 1. The epoxy resin A, the phenolic resin A, the curing accelerator, the inorganic filler, and the silane coupling agent A are as follows. Epoxy resin A: Bisphenol A type epoxy resin (product name "JER (registered trademark) 1001", manufactured by Mitsubishi Chemical Corporation) Phenolic resin A (hardener): Novolac type phenolic resin (product name "GS-200", manufactured by Gun-ei Chemical Co., Ltd.) Curing accelerator: Tetraphenylphosphonium tetraphenylborate (TPP-K (registered trademark), manufactured by Hokko Chemical Industry Co., Ltd.) · Inorganic filler: Boron nitride filler (BN filler) Silane coupling agent A: A block copolymer of a first polybutadiene block composed of an addition polymer of unsubstituted butadiene having no functional groups, a second polybutadiene block composed of an addition polymer of butadiene having an acid anhydride group, and a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group (product name "X-12-1287A", manufactured by Shin-Etsu Silicones). The epoxy resin A and the phenolic resin A were contained in the resin composition at an equivalent ratio of 1:1. The curing accelerator was contained in the resin composition in an amount of 0.01 part by mass per 100 parts by mass of the total of the epoxy resin A and the phenol resin A. Furthermore, an inorganic filler was contained in the resin composition so that the content of the inorganic filler was 59.0 parts by volume when the solid content of the cured product of the resin composition after curing was taken as 100 parts by volume. The silane coupling agent A was contained in an amount of 0.015% by mass relative to the mass of the inorganic filler contained in the resin composition.

[0073] Example 2 A resin composition according to Example 2 was obtained in the same manner as in Example 1, except that silane coupling agent B was used instead of silane coupling agent A as the silane coupling agent for treating the inorganic filler before kneading. As the silane coupling agent B, a block copolymer (product name "X-12-1267B", manufactured by Shin-Etsu Silicones) consisting of a polybutadiene block and a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group was used.

[0074] Example 3 A resin composition according to Example 3 was obtained in the same manner as in Example 1, except that silane coupling agent C was used instead of silane coupling agent A as the silane coupling agent for treating the inorganic filler before kneading. As the silane coupling agent C, a block copolymer (product name "X-12-1267B-ES", manufactured by Shin-Etsu Silicones) consisting of a polybutadiene block and a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group was used.

[0075] Comparative Example 1 A resin composition according to Comparative Example 1 was obtained in the same manner as in Example 1, except that silane coupling agent D was used instead of silane coupling agent A as the silane coupling agent for treating the inorganic filler before kneading. As the silane coupling agent D, 3-glycidoxypropyltrimethoxysilane (product name "KBM-403", manufactured by Shin-Etsu Silicones Co., Ltd.) was used.

[0076] Comparative Example 2 A resin composition according to Comparative Example 2 was obtained in the same manner as in Example 1, except that silane coupling agent E was used instead of silane coupling agent A as the silane coupling agent for treating the inorganic filler before kneading. As the silane coupling agent E, glycidoxyoctyltrimethoxysilane (product name "KBM-4803", manufactured by Shin-Etsu Silicones Co., Ltd.; a long-chain spacer type silane coupling agent) was used.

[0077] Comparative Example 3 A resin composition according to Comparative Example 3 was obtained in the same manner as in Example 1, except that silane coupling agent F was used instead of silane coupling agent A as the silane coupling agent for treating the inorganic filler before kneading. As the silane coupling agent F, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (product name "KBM-603", manufactured by Shin-Etsu Silicones Co., Ltd.) was used.

[0078] Comparative Example 4 A resin composition according to Comparative Example 4 was obtained in the same manner as in Example 1, except that silane coupling agent G was used instead of silane coupling agent A as the silane coupling agent for treating the inorganic filler before kneading. As the silane coupling agent G, 3-aminopropyltrimethoxysilane (product name "KBM-903", manufactured by Shin-Etsu Silicones Co., Ltd.) was used.

[0079] <Thermal conductivity> For the measurement of thermal conductivity, an insulating and heat-dissipating sheet was prepared as follows. First, the base material, copper foil (area: 2500 cm 2 ) was coated with the resin composition according to each example (thickness: about 200 μm). The coating method was a roll-to-roll coater method, and the drying conditions were 120° C. and 5 minutes. In this manner, a resin sheet was produced for each of the resin compositions according to each example. Next, for each of the resin sheets according to each example, two of the same type of resin sheets were stacked together with the surfaces not in contact with the substrate facing each other, and then heat pressed at a temperature of 100°C, a pressure of 8 MPa, and a time of 20 minutes to produce an insulating heat dissipation sheet with metal foil (insulating layer thickness 0.22±0.04 mm).

[0080] The copper foil, which was the metal foil, was removed from both sides of the insulating heat dissipation sheet by etching, and a rectangular resin cured body was cut out from this insulating heat dissipation sheet with each side measuring 10 mm ± 0.5 mm. An anti-reflective agent (manufactured by Fine Chemical Japan Co., Ltd., product number: FC-153) was applied to both sides of the cut-out cured resin body to prepare a sample for measuring thermal diffusivity. The thermal conductivity value was calculated by multiplying the thermal diffusivity value measured for the thermal diffusivity measurement sample using a xenon flash analyzer (NETZSCH, LFA-447 type) by the specific heat value measured by heat flux DSC in accordance with JIS 7123:1987, and the density value measured by the immersion method in accordance with JIS K 7122:1999. The thermal diffusivity value was calculated by arithmetic averaging the thermal diffusivity values ​​measured for three measurement samples. In addition, the thermal diffusivity was measured at five points for each measurement sample, and the arithmetic average of the three values ​​excluding the maximum and minimum values ​​for each measurement sample was used as the measured value. The results of measuring the thermal conductivity are shown in Table 1 below.

[0081] <Peel strength> The resin composition according to each of the above examples was applied to one side of an electrolytic copper foil (thickness: 35 μm) to prepare two sheets having a resin layer (thickness: 145 μm). Next, the two sheets were hot-pressed (3.0 MPa, 120°C, 20 min) to bond the resin layers together, and one copper foil was peeled off from the back surface of the sheet. An aluminum plate was then placed on the surface from which the copper foil had been peeled off, and the sheet was transferred to the aluminum plate by hot pressing (2.0 MPa, 120°C, 20 min), and the copper foil was then peeled off from the sheet to obtain a semi-cured sheet. Next, the adherend (1 oz copper foil) was laminated onto this semi-cured sheet, and the resin layer and adherend were integrated by heat pressing (2.0 MPa, 180°C, 120 min). After the resin layer was sufficiently cured, it was cut into a size of 20 mm x 100 mm, and the cut-out adherend was processed (etched) to a width of 10 mm to prepare a test piece for the peel test. The test pieces were subjected to a 90° peel test at a peeling speed of 50 mm / min, and the adhesive strength between the adherend and the resin layer was evaluated based on the peel strength. The peel strength was measured and the results are shown in Table 1 below.

[0082] <Dielectric breakdown strength (BDV)> The dielectric breakdown strength was measured using a dielectric breakdown device that has a crest factor between 1.34 and 1.48, can apply a voltage at a frequency of 50 or 60 Hz, and has a maximum voltage of AC 10 kV (effective value). Details of the measurement method will be described with reference to Figs. 1 and 2. The copper foil on one side of a thermally conductive sheet measuring 75±1 mm×65±1 mm was peeled off to obtain a resin sheet, and an aluminum plate was laminated on the surface of the resin sheet from which the copper foil 13 had been peeled off, followed by heating to obtain a laminated sheet in which the aluminum plate was integrated with the resin sheet. Next, the laminated sheet was further heated to completely harden the resin sheet, thereby obtaining a dielectric breakdown strength measurement sample 14 shown in FIG. 1. The resin sheet was produced using the resin composition according to each example. 2, the dielectric breakdown strength measurement sample 14 was placed on a brass disk electrode 17 (Φ: 40 mm) with the aluminum plate side facing down in insulating oil 16 (JIS C2320:1999) in an oil tank 15, and a brass spherical electrode 18 (Φ: 15 mm, weight: 50 g) was placed on top of the dielectric breakdown strength measurement sample 14 so as to contact the approximate center of the dielectric breakdown strength measurement sample 14. The insulating oil 16 was kept at 20±10°C, and a voltage was continuously applied to the dielectric breakdown strength measurement sample 14 at a voltage increase rate of 1 kV (effective value) / sec until dielectric breakdown occurred. As a criterion for determining dielectric breakdown, a cutoff current was set to 25 mA. The voltage (unit: kV) at which dielectric breakdown occurred was divided by the thickness (unit: mm) of the dielectric breakdown strength measurement sample 14 to determine the dielectric breakdown strength. The results of measuring the dielectric breakdown strength (BDV) are shown in Table 1 below.

[0083] <Dielectric strength> The withstand voltage was measured using a dielectric breakdown device that has a crest factor between 1.34 and 1.48, can apply a voltage at a frequency of 50 or 60 Hz, and has a maximum voltage of AC 10 kV (effective value). Details of the measurement method will be described with reference to Figs. 1 and 2. The copper foil 13 on one side of the insulating heat dissipation sheet of 75±1 mm×65±1 mm was peeled off, and an aluminum plate was laminated on the peeled surface and heated to integrate the aluminum plate with the insulating heat dissipation sheet, and further heated to completely harden the laminate, thereby obtaining the voltage resistance measurement sample 14 shown in FIG. 1. The insulating heat dissipation sheet was prepared with the resin composition according to each example. As shown in FIG. 2, the voltage resistance measurement sample 14 was placed on a brass disk electrode 17 (Φ: 40 mm) with the aluminum plate side facing down in insulating oil 16 (JIS C2320:1999) in an oil tank 15, and a brass spherical electrode 18 (Φ: 15 mm, weight: 50 g) was placed on the voltage resistance measurement sample 14 so as to contact the approximately center part of the voltage resistance measurement sample 14. The insulating oil 16 was kept at 20±10° C., and AC 3.0 kV (effective value) was applied to the voltage resistance measurement sample 14 for 1 minute. If no dielectric breakdown occurred, the voltage was immediately increased to AC 0.5 kV (effective value) and applied for 1 minute, and then increased in 0.5 kV (effective value) intervals (0.5 kV (effective value) steps, applied for 1 minute) until dielectric breakdown occurred. As a criterion for determining whether dielectric breakdown occurred, a cutoff current was set to 10 mA. The withstand voltage was calculated by dividing the applied voltage, which was 0.5 kV (effective value) lower than the voltage at which dielectric breakdown occurred, by the thickness (unit: mm) of the withstand voltage measurement sample 14. The withstand voltage of each example was measured and the results are shown in Table 1 below.

[0084] [Table 1]

[0085] <Thermal conductivity> As shown in Table 1, the resin composition of Example 1 has an improved thermal conductivity of the cured product compared to the resin compositions of each of the comparative examples, and the resin compositions of Examples 2 and 3 have approximately the same thermal conductivity of the cured product compared to the resin compositions of each of the comparative examples. In addition, in each of the resin compositions according to the examples, the thermal conductivity of the cured product was extremely high, exceeding 10 W / (m·K). This shows that the use of a silane coupling agent having a polybutadiene structure can provide a sufficiently high thermal conductivity for the cured product.

[0086] <Peel strength> As shown in Table 1, it is clear that the resin compositions according to the respective Examples have significantly improved peel strength compared to the resin compositions according to the respective Comparative Examples. In particular, the resin compositions according to Examples 2 and 3 exhibited high peel strength values ​​exceeding 3 N / cm. In addition, the occurrence of cohesive failure was observed in the resin compositions according to the respective comparative examples. This shows that the peel strength can be significantly improved by using a silane coupling agent having a polybutadiene structure.

[0087] <Dielectric breakdown strength (BDV) and withstand voltage> Furthermore, as shown in Table 1, the resin compositions according to each Example exhibited values ​​for at least one of the dielectric breakdown strength (BDV) and the voltage resistance comparable to those of the resin compositions according to each Comparative Example. From this, it is understood that by using a silane coupling agent having a polybutadiene structure, the dielectric breakdown strength (BDV) and withstand voltage can be made to exhibit relatively high values. [Explanation of symbols]

[0088] 13 copper foil, 14 measurement samples (dielectric breakdown strength measurement sample, voltage endurance measurement sample), 15 oil tank, 16 insulating oil, 17 brass disk electrode, 18 brass spherical electrode.

Claims

1. A resin composition comprising an epoxy resin, a silane coupling agent, a curing agent, and an inorganic filler, the inorganic filler being dispersed in the epoxy resin, The silane coupling agent has a polybutadiene structure and is a block copolymer having a plurality of blocks, The block copolymer comprises a polybutadiene block, The resin composition further comprises a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group at both molecular terminals.

2. The block copolymer is a first polybutadiene block composed of an addition polymer of unsubstituted butadiene having no functional group; and a second polybutadiene block composed of an addition polymer of butadiene having an acid anhydride group. The resin composition according to claim 1.

3. The inorganic filler includes a boron nitride filler. The resin composition according to claim 1 or 2.

4. A thermally conductive sheet including a resin layer made of a resin composition containing an epoxy resin, a silane coupling agent, a curing agent, and an inorganic filler, the inorganic filler being dispersed in the epoxy resin, The silane coupling agent has a polybutadiene structure and is a block copolymer having a plurality of blocks, The block copolymer comprises a polybutadiene block, The thermally conductive sheet further comprises a block composed of an addition polymer of a compound having a vinyl group and an alkoxysilyl group at both molecular terminals.

5. The block copolymer is a first polybutadiene block composed of an addition polymer of unsubstituted butadiene having no functional group; and a second polybutadiene block composed of an addition polymer of butadiene having an acid anhydride group. The thermally conductive sheet according to claim 4 .

6. The inorganic filler includes a boron nitride filler. The thermally conductive sheet according to claim 4 or 5.

Citation Information

Patent Citations

  • Epoxy resin composition and semiconductor device

    JP2001123050A

  • Insulation sheet and laminated structural body

    JP2009231249A

  • Manufacturing method of insulating sheet

    JP2010094887A

  • Silane-modified copolymer, method for producing the same, and adhesion improver

    JP2018039909A